Action (1893) : Essay on a Critique of Life and a Science of Practice - Blondel, Maurice, 1861-1949 (Book collections on Project MUSE., 2021)
"Action was once a prominent theme in philosophical reflection. It figured prominently in Aristotelian philosophy, and the medieval Scholastics built some of their key adages around it. But by the time Maurice Blondel came to focus on it for his own philosophical reflection, it had all but disappeared from the philosophical vocabulary. It is no longer possible or legitimate to ignore action in philosophy as it was in France when Blondel appeared on the scene in 1882, when at the age of 21 he first began to focus on action as a dissertation subject, and in 1893, when he defended and published the dissertation now presented here for the English reader." --